Promoting Students’ Academic Achievement on Difficult Biology Concepts Using Context-Based Instructional Method: Implication for Reducing Depression Among Students - Okereke, Innocent; Ogu, Bala; Olori, Gloria; Olori, Christian (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2024)
Poor achievement of students in Biology, as reported by the West African Examination Council chief examiner in 2022 and 2023 in Nigeria, as well as the fluctuating trend in the achievement of Biology students over the years, necessitate the need for the present study. The study adopted the quasi-experimental design using the pretest-posttest non-equivalent control group design. The study was guided by three specific purposes and hypotheses, with a population of 673 senior secondary two (SS2) biology students. The sample size of 120 participants (M=55; F=65) was drawn using a simple random sampling technique. Data were collected with a validated Biology Achievement Test (BAT) that has a reliability value of 0.93, determined using K-R21 Mean and standard deviation were used to answer the research questions, while ANCOVA was used to test the hypotheses at 0.05 significant level. Results show that students taught difficult biology concepts with a context-based instructional method outperformed those taught with the conventional lecture method. The difference in the mean achievement scores of male and female students was not significant and there was also no significant interaction effect of teaching method and gender on students’ achievement in biology.